The serum uric acid level in females may be a better indicator of metabolic syndrome and its components than in males in a Japanese population . Issue 1 (July 2020) - Tani, Shigemasa; Matsuo, Rei; Imatake, Kazuhiro; Suzuki, Yasuyuki; Takahashi, Atsuhiko; Yagi, Tsukasa; Matsumoto, Naoya; Okumura, Yasuo
Highlights: Increased uric acid (UA) level in females is related to metabolic syndrome (Mets). Few data exist on the association of serum UA level with Mets in Japanese by sex. Serum UA level may be a more reliable marker of Mets in females even in Japanese. This may be related to a sex difference in abdominal obesity and UA level with age. Abstract: Background: Although the level of uric acid (UA) is higher in males, increased UA level in females was reported to be closely associated with prevalence of metabolic syndrome (Mets) leading to atherosclerotic cardiovascular disease (ASCVD). Few data exist regarding the gender diferences in relationship between the serum UA levels and cardo-metabolic risk in the Japanese population, which generally contains a lower proportion of obesity than Western populations. Methods: This cross-sectional study was designed to investigate, by gender, the association between the serum UA level and abdominal obesity, and thereby cardio-metabolic risk i.e. presence of Mets and its components using a sample of 8567 apparently healthy subjects females: n = 3334, males: n = 5233 at the Health Planning Center of Nihon University Hospital between September 2015 and August 2016. Results: Receiver operating characteristic analysis was performed to reveal the accuracy of serum UA level as a predictor of abdominal obesity based on the Japanese criteria of Mets (females vs. males: area under the curve, 0.751 vs 0.609). Furthermore, the serum UA level and proportion of abdominal obesity rose with increasing age in females; in males, however, these parameters did not change in parallel with age. Furthermore, the serum UA levels in females reflected a status of cardio-metabolic risk when compared with males in a multi-logistic regression analysis. It is particularly worth noting that in the above-mentioned multivariate logistic regression analysis, the odds ratio of hyperuricemia in females was generally 1.3–2.5 times higher than that in males. Conclusions: Compared with males, increased serum UA level in females might be involved in abdominal obesity and cardio-metabolic risk, possibly leading to the development of ASCVD even in a Japanese population. This may be due to gender differences affecting the development of abdominal obesity and changes in the serum UA levels with age. Clinical Trial Registration: UMIN (http://www.umin.ac.jp/ ) Study ID:　UMIN000035901retrospectively registered 1 March 2018.